Development and characterization of Nile tilapia (Oreochromis niloticus) protein isolate-based biopolymer films incorporated with essential oils and nanoclay. (September 2020) - da Silva Scudeler, Cintia Granzotti; de Lima Costa, Thayná; Cortez-Vega, William Renzo; Prentice, Carlos; Fonseca, Gustavo Graciano
Graphical abstract: Highlights: This work aimed to produce and characterise biofilms based on recovered fish protein. The increase of the protein isolate (HSPI) decreased the solubility in water of the films. The increase of the HSPI increased the solubility in acid and tensile strength of the films. Higher opacity was observed with higher values HSPI and clove essential oil (CEO). The film with the best characteristics had 25 % glycerol, 2.5 g HSPI and 0.5 g CEO. Abstract: Fish residues are a natural resource of valuable components, e.g. proteins. The aim of this work was to develop biopolymer films from Nile tilapia ( Oreochromis niloticus ) protein isolate (NTPI), incorporated with glycerol, montmorillonite nanoclay, and essential oils. The extracted protein was characterized for its isoelectric potential, proximate composition, solubility, water retention capacity (WRC), oil retention capacity (ORC), and color. The casting technique was utilized to obtain the films. Experiments were conducted using a 2 (5–1) factorial design with central point. The films were characterized for thickness, solubility in water (Sw), solubility in acid (Sa), water vapor permeability (WVA), and mechanical, structural, and thermal properties. The protein isolate concentered 85 % of the total protein from the raw material. Glycerol, nanoclay, and clove and oregano essential oils were successfully incorporated to the films. The films with the best characteristics were obtained with T6 (1.5 g NTPI, 0.2 g glycerol, 0.4 g oregano essential oil, 0.3 of nanoclay), and T12 (1.5 g NTPI, 0.4 g glycerol, 0.4 g clove essential oil, 0.1 g nanoclay) because they were more stabilized within the cross-linking protein structure. The increase of the protein isolate decreased the Sw of the films but increased the Sa and tensile strength. The Sw ranged from 30.62 to 85.45 %, the Sa between 13.19 and 45.92 %, the WVP between 2.38 and 4.02 g mm/kPa day m 2 . Tensile strength ranged from 0.65 to 2.76 MPa and elongation from 0.29 to 2.07 %. The essential oils did not show antimicrobial activity when incorporated to the polymer matrix of the films.